2011
DOI: 10.1002/yea.1838
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of the UDP‐glucosyltransferase UgtB1 involved in sophorolipid production by Candida bombicola and creation of a glucolipid‐producing yeast strain

Abstract: Sophorolipids produced by the non-pathogenic yeast Candida bombicola ATCC 22214 are glycolipid biosurfactants applied commercially as biodegradable and eco-friendly detergents. Their low cell toxicity, excellent wetting capability and antimicrobial activity attract the attention of high-value markets, such as the cosmetic and pharmaceutical industries. Although sophorolipid production yields have been increased by the optimization of fermentation parameters and feed sources, the biosynthetic pathway and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 56 publications
2
81
0
Order By: Relevance
“…All rights reserved 8 E n z y m e a s s a y s S. bombicola ATCC 22214 wild type, the ugtA1 deletion mutant A113 knocked out in the first glucosyltransferase (Saerens et al 2011a) and the ugtB1 deletion mutant B11 knocked out in the second glucosyltransferase (Saerens et al, 2011c) were grown overnight in 5mL 3C medium at 30°C and 200 rpm. The culture was used to inoculate 20 mL 3C medium and was incubated the same way for about 60 hours.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…All rights reserved 8 E n z y m e a s s a y s S. bombicola ATCC 22214 wild type, the ugtA1 deletion mutant A113 knocked out in the first glucosyltransferase (Saerens et al 2011a) and the ugtB1 deletion mutant B11 knocked out in the second glucosyltransferase (Saerens et al, 2011c) were grown overnight in 5mL 3C medium at 30°C and 200 rpm. The culture was used to inoculate 20 mL 3C medium and was incubated the same way for about 60 hours.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…The deletion fragments were transformed as previously reported by Saerens et al . (,b). The yeast cells (10 7 per ml) were inoculated into a 100‐ml Erlenmeyer flask containing 30 ml seed medium and incubated at 28–30°C, with shaking at 220 rpm for 2 days until the medium turned milky.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that both glucosyltransferases were inhibited by their product SLs. Further, when the product concentration reached > 1 mM, the residual activity observed for UgtA1 was only 62% (Saerens et al ., ,b). Moreover, Haque et al .…”
Section: Introductionmentioning
confidence: 99%
“…This activates the fatty acid for the addition of glucose by glucosyltransferase I, using uridine diphosphate (UDP)‐glucose as donor molecule (UgtA1; ). The second glucose is linked to the first via a glucosyl‐β‐(1,2)‐glucosyl linkage by glucosyltransferase II (UgtB1; ). The product of the second glycosylation, a nonacetylated SL, can be further decorated with one or two acetyl groups at the C6′ or C6″ position of the sophorose moiety.…”
Section: Sophorolipidsmentioning
confidence: 99%
“…Furthermore, the single knockout strategy resulted in a transformant capable of producing glucolipids rather than SLs; only the first of the two glucose units is attached to the fatty acid backbone. To this end, the ugtb1 gene was interrupted . Not only can the hydrophilic head be tailored through genetic engineering of the production host, also the hydrophobic tail of the SLs can be adjusted; by exchanging the C18‐prone Cyp52m1 responsible for hydroxylation of the fatty acid with C 16 ‐specific‐P450 enzymes, SLs with shorter fatty acid tails were obtained .…”
Section: Sophorolipidsmentioning
confidence: 99%